Helminth Community Structure of Tits Cyanistes caeruleus and Parus major (Paridae) during Their Autumn Migration on the Southern Baltic Coast - Izabella Rząd; Anna Okulewicz; Rusłan Sałamatin; Magdalena Szenejko; Remigiusz Panicz; Jarosław K. Nowakowski; Agata Stapf (Animals, 2023)
The research problem undertaken in this study is to determine the scale of infection of Eurasian blue tit Cyanistes caeruleus and Great tit Parus major and the biological diversity of their internal parasites, helminths. The aim of the study is to gain new knowledge about the structure of the helminth communities of the Eurasian blue tit and Great tit on the southern coast of the Baltic Sea during autumn migration to their wintering grounds. Helminths of tits were collected in 2008–2012 on the southern coast of the Baltic Sea in Poland. PAST v. 2.11 software was used for the calculations. Barcoding DNA was used to identify trematodes initially classified based on morphological characters to the genera Leucochloridium and Urogonimus. Cestodes Anonchotaenia globata were recorded for the first time in Poland. The Eurasian blue tit is a new host in Poland for three species of helminths: cestode Monosertum parinum and filarial nematodes, Cardiofilaria pavlovskyi, and Diplotriaena henryi. The Great tit is a new host in Poland for trematode Urogonimus macrostomus, cestode A. globata and M. parinum, and filarial nematode Diplotriaena obtusa. The nematode C. pavlovskyi was the species most frequently recorded in both host species. A high degree of similarity was found between the component communities and infracommunities of helminths in Eurasian blue tit and Great tit. The new information provided in this study has increased our knowledge of the transmission of helminths in Central Europe.